Post-operative C-reactive protein profile following abdominal wall reconstruction with transversus abdominis posterior components separation. (2017) - Pearce, A.; Thornton, L.; Sutton, P.A.; Walsh, C.J.
Highlights: AWRTAR is becoming a popular surgical technique used within large abdominal wall hernia repair. Post-operative CRP values are significantly greater in these unique patients. This CRP nomogram aids clinicians in the early detection of post-operative complications. Abstract: Introduction: Abdominal wall reconstruction using posterior component separation with transversus abdominis release (AWTAR) produces a unique post-operative CRP profile, when compared to routine elective colorectal operations. Therefore, we aim to establish the normal post-operative C-reactive protein (poCRP) profile following AWRTAR and reduce the unnecessary invasive interventions in patients already at greater risk of septic complications. Methods: A retrospective analysis of daily poCRP levels was performed both for patients who underwent uncomplicated AWRTAR (n = 12), and a comparator group of uncomplicated open right hemicolectomies (RH) matched for age and sex (n = 24). All operations in both groups were performed by a single surgeon from 2013 to 2015. Results: The median (IQR) age was 62 (16) and 67 (16) years respectively, with a higher proportion of males to females in both groups (10:2 vs . 17:7). The poCRP profile follows an initial steep rise, peaking at day 2 followed by a gradual washout phase. The poCRP peak is significantly greater in the AWRTAR group compared to the RH group (274 [95%CI ±25] vs . 160 [95%CI ± 27]; p = 0.0001), with a positive correlation between day 2 CRP levels and operative length (r = 0.56). Conclusions: We have demonstrated that uncomplicated AWRTAR provokes a significantly greater poCRP rise (>200) compared to that well described in the literature for uncomplicated open colectomy. As poCRP is an important marker of post-operative recovery with abnormally high levels associated with septic complications, these data should help clinicians interpret the post-operative clinical course after AWRTAR.